2017
DOI: 10.1186/s40560-017-0215-2
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced cardiac dysfunction and β-adrenergic blockade therapy for sepsis

Abstract: Despite recent advances in medical care, mortality due to sepsis, defined as life-threatening organ dysfunction caused by a dysregulated host response to infection, remains high. Fluid resuscitation and vasopressors are the first-line treatment for sepsis in order to optimize hemodynamic instability caused by vasodilation and increased vascular permeability. However, these therapies, aimed at maintaining blood pressure and blood flow to vital organs, could have deleterious cardiac effects, as cardiomyocyte dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 88 publications
1
79
0
3
Order By: Relevance
“…1 Dr Berk Takir et al argue that presence of sepsis or septic shock instead of (or due to) CAP may have influenced our findings by referring to evidence showing that the degree of sepsis-induced cardiac dysfunction is an important prognostic factor in critically ill patients. 2 Our study was conducted in a subset (n = 295) of a cohort of (n = 304) patients hospitalized with CAP in a non-academic teaching hospital. 1 Direct intensive care unit (ICU) admission was an exclusion criterion.…”
Section: From the Authorsmentioning
confidence: 99%
“…1 Dr Berk Takir et al argue that presence of sepsis or septic shock instead of (or due to) CAP may have influenced our findings by referring to evidence showing that the degree of sepsis-induced cardiac dysfunction is an important prognostic factor in critically ill patients. 2 Our study was conducted in a subset (n = 295) of a cohort of (n = 304) patients hospitalized with CAP in a non-academic teaching hospital. 1 Direct intensive care unit (ICU) admission was an exclusion criterion.…”
Section: From the Authorsmentioning
confidence: 99%
“…β adrenerjik reseptörlerin aktivitesi kendi içerisinde denge oluşturur. β1 aktivitesi ile TNF-a, IL-1β gibi proinflamatuar sitokinlerin salınımı artarken; b2 reseptörlerin çalışması bu salınımı suprese eder (20). Sepsiste ise bir sitokin fırtınası durumu söz konusudur.…”
Section: Gereç Ve Yöntemunclassified
“…Contentious aspects of that trial including liberal levosimendan use and high mortality in the standard care arm have reduced validity of the findings. Nonetheless, evidence of potential beneficial effects of beta‐blockade on microcirculation and cardiac function is accumulating, and results of clinical trials underway are awaited . The novel calcium‐sensitising agent levosimendan is a non‐catecholamine inotropic agent also examined in sepsis.…”
Section: Haemodynamic Organ Supportmentioning
confidence: 99%
“…Nonetheless, evidence of potential beneficial effects of beta-blockade on microcirculation and cardiac function is accumulating, and results of clinical trials underway are awaited. 59 The novel calcium-sensitising agent levosimendan is a non-catecholamine inotropic agent also examined in sepsis. Despite several small trials and a positive meta-analysis, 60 levosimendan was not found beneficial for patients with septic shock in the LeoPARDS RCT.…”
Section: Other Cardiovascular Therapiesmentioning
confidence: 99%